A high-efficiency, information-based exploration path planning method for active simultaneous localization and mapping. (13th February 2020) - Li, Peng; Yang, Cai-yun; Wang, Rui; Wang, Shuo
The efficiency of exploration in an unknown scene and full coverage of the scene are essential for a robot to complete simultaneous localization and mapping actively. However, it is challenging for a robot to explore an unknown environment with high efficiency and full coverage autonomously. In this article, we propose a novel exploration path planning method based on information entropy. An information entropy map is first constructed, and its boundary features are extracted. Then a Dijkstra-based algorithm is applied to generate candidate exploration paths based on the boundary features. The dead-reckoning algorithm is used to predict the uncertainty of the robot's pose along each candidate path. The exploration path is selected based on exploration efficiency and/or high coverage. Simulations and experiments are conducted to evaluate the proposed method's effectiveness. The results demonstrated that the proposed method achieved not only higher exploration efficiency but also a larger coverage area.